2017
DOI: 10.1007/s00425-017-2781-x
|View full text |Cite
|
Sign up to set email alerts
|

One-third of the plastid genes evolved under positive selection in PACMAD grasses

Abstract: We demonstrate that rbcL underwent strong positive selection during the C -C photosynthetic transitions in PACMAD grasses, in particular the 3' end of the gene. In contrast, selective pressures on other plastid genes vary widely and environmental drivers remain to be identified. Plastid genomes have been widely used to infer phylogenetic relationships among plants, but the selective pressures driving their evolution have not been systematically investigated. In our study, we analyse all protein-coding plastid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
104
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(124 citation statements)
references
References 62 publications
15
104
2
Order By: Relevance
“…K a /K s values >1, =1, and <1 indicate positive selection, natural evolution and purifying selection, respectively (Lawrie et al, 2013), while a minimal ratio of K a /K s (<0.5) in many genes represents purifying selection working on them. Many proteins and RNA molecules encoded by the chloroplast genomes are under purifying selection since they are involved in important functions of plant metabolism, self-replication and photosynthesis and therefore play a pivotal role in plant survival (Piot et al, 2018). Departure from the main purifying selection in case of plastid genes might happen in response to certain environmental changes when advantageous genetic mutations might contribute to survival and better adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…K a /K s values >1, =1, and <1 indicate positive selection, natural evolution and purifying selection, respectively (Lawrie et al, 2013), while a minimal ratio of K a /K s (<0.5) in many genes represents purifying selection working on them. Many proteins and RNA molecules encoded by the chloroplast genomes are under purifying selection since they are involved in important functions of plant metabolism, self-replication and photosynthesis and therefore play a pivotal role in plant survival (Piot et al, 2018). Departure from the main purifying selection in case of plastid genes might happen in response to certain environmental changes when advantageous genetic mutations might contribute to survival and better adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…Several regions highlighted as hyper or moderately variable regarding the nucleotide diversity values across Opuntioideae chloroplast sequences (i.e., accD, ycf1, clpP, petD, rpl32 and ccsA) have been reported to be putatively under positive selection in some lineages, such as Brassicaceae, Bignoniaceae, Rutaceae, Orchidaceae, Geraniaceae and Poaceae (Hu et al 2015;Weng et al 2016;Dong et al 2018;Carbonell-Caballero et al 2015;Ruhlman and Jansen 2018;Thode & Lohmann 2019;Park et al 2017;Piot et al 2018). Positive selection may come into play in response to environmental changes (Piot et al 2018). For example, the accD gene, which encodes the β -carboxyl transferase subunit of acetyl-CoA carboxylase, is an essential and required component for plant leaf development (Kode et al 200), and it is suggested to have played a pivotal role in the adaptive evolution of orchids (Dong et al 2018).…”
Section: Insights From Chloroplast Genome Assemblies In Opuntioideae mentioning
confidence: 99%
“…We also found three genes under positive selection in the chloroplast genome of S. bogneri, including ycf2, clpP, and rpl36, which might be due to the different types of stresses faced by these species in their respective ecological niches. These genes were also found to be under positive selection in various other species [11,16,55,66,67].…”
Section: Comparative Genomics Among De Novo Assembled Chloroplast Genmentioning
confidence: 99%
“…The amino acid frequency analyses revealed high encoding of leucine, whereas the rarest encoding was recorded for cysteine ( Figure S1). The RNA editing analyses revealed the presence of [62][63][64][65][66][67][68][69][70][71][72][73][74] RNA editing sites in 19-21 genes (Table S4). The RNA editing sites were found in the same genes with a few exceptions: RNA editing sites were detected in psaB genes of only Z. zamiifolia, whereas the RNA editing site was not found in rpl20 of S. bogneri and rps8 of L.…”
Section: Analyses Of Codon Usage Amino Acid Frequency and Rna Editingmentioning
confidence: 99%
See 1 more Smart Citation